Halloweentown double feature [videorecording (DVD)] - Brown, Kimberly J.; Reynolds, Debbie; Hoag, Judith (Buena Vista Home Entertainment, 2005)
Once Marnie learns she is a witch, her grandmother Aggie guides her through a series of adventures in Halloweentown, a magical place where ghosts, ghouls and werewolves are real.